Invasões Francesas e Pré-Romantismo Português - Francofobia e Anglomania - Álvaro Manuel Machado (Carnets)
While the real and historic invasions of Portugal by Napoleon were taking place, between the years 1807 and 1810, we can also note two other evasions: a real and historical one – the royal family’s escape to Brazil – and an imaginary, but equally real, one: the birth of Portuguese Pre-Romanticism, clearly dependent on an Enlightenment and revolutionary image of the Revolutionary France, which will then be lost with the French invasion. As a consequence, a widespread francophobia arises, which would last until the liberal revolution in 1820. From then on, the idealized image of England grows stronger and English works start being translated from, ironically, French versions.